2020
DOI: 10.32942/osf.io/gsz7j
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Directed evolution of microbial communities

Abstract: Directed evolution is a form of artificial selection that has been used for decades to find biomolecules and organisms with new or enhanced functional traits. Directed evolution can be conceptualized as a guided exploration of the genotype-phenotype map, where genetic variants with desirable phenotypes are first selected and then mutagenized to search the genotype space for an even better mutant. In recent years, the idea of applying artificial selection to microbial communities has gained momentum. Here, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Those differences in community composition that are due to transient ecological dynamics (i.e., to communities not being in equilibrium), stochastic fluctuations in species abundances, rapid and random fluctuations in environmental conditions, or simply experimental error in determining the function of all communities will not contribute to the success of artificial selection (Blouin et al 2015;Penn and Harvey 2004;Chang et al 2020). Quite the contrary: if strong enough, these nonheritable sources of variation can mask the heritable variation, diminishing heritability and therefore the response to selection (Blouin et al 2015;Chang et al 2020;Sanchez et al 2020). Therefore, future attempts to apply artificial selection at the community level should take great care to minimize those sources of variation, for instance, as we have recently discussed at length, ensuring that the environment is as stable as possible, and that communities are in a generationally stable state before selection is applied (Chang et al 2020;Penn and Harvey 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those differences in community composition that are due to transient ecological dynamics (i.e., to communities not being in equilibrium), stochastic fluctuations in species abundances, rapid and random fluctuations in environmental conditions, or simply experimental error in determining the function of all communities will not contribute to the success of artificial selection (Blouin et al 2015;Penn and Harvey 2004;Chang et al 2020). Quite the contrary: if strong enough, these nonheritable sources of variation can mask the heritable variation, diminishing heritability and therefore the response to selection (Blouin et al 2015;Chang et al 2020;Sanchez et al 2020). Therefore, future attempts to apply artificial selection at the community level should take great care to minimize those sources of variation, for instance, as we have recently discussed at length, ensuring that the environment is as stable as possible, and that communities are in a generationally stable state before selection is applied (Chang et al 2020;Penn and Harvey 2004).…”
Section: Discussionmentioning
confidence: 99%
“…2020; Sanchez et al. 2020). Therefore, future attempts to apply artificial selection at the community level should take great care to minimize those sources of variation, for instance, as we have recently discussed at length, ensuring that the environment is as stable as possible, and that communities are in a generationally stable state before selection is applied (Chang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies of artificial selection have demonstrated that it is possible to steer microbiota across generations to modify microbial ecosystems properties [4][5][6][7][8] . In some cases, the selected property can be a trait displayed by the host of a microbiota, like with microbial communities associated to plants 5,[10][11][12][13] .…”
Section: Main Textmentioning
confidence: 99%
“…In some cases, the selected property can be a trait displayed by the host of a microbiota, like with microbial communities associated to plants 5,[10][11][12][13] . This opens new avenues for plant breeding via directional artificial selection of rhizosphere microbiota [1][2][3][4] . Still, while previous studies reported significant selection effects 6,7,11 , the selected property may not be perennial and lost during the process 6,9 .…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation